Discussion of Violence in Psychiatric Evaluations - Gondolf, E. W. (Journal of interpersonal violence, 1992)
Psychiatric practitioners and family violence specialists expect that violence will be substantially discussed during the course of psychiatric evaluations in order to assess potential dangerousness. Research on medical discourse implies that violence is likely to be minimized by medical staff, but the actual psychiatric discussion of violence has not been empirically investigated. This study examines the major transactions regarding violence during the course of transcribed psychiatric evaluations for 92 recently violent patients from a population of 382 psychiatric patients. The severity of the reported violence, the introduction of the violence, the clinician follow-up, the case presentation, the psychiatrist follow-up, and treatment options are each categorically coded for their mentions of patient violence. The transactions are also cross-tabulated to identify significant contributors to subsequent mention of violence. The findings substantiate a progressive decrease in the discussion of violence and apparent breaches in the flow of information regarding violence. Protocol innovations to assure adequate discussion of violence are recommended